Small airways obstruction and its risk factors in the Burden of Obstructive Lung Disease (BOLD) study: a multinational cross-sectional study. Issue 1 (January 2023) - Knox-Brown, Ben; Patel, Jaymini; Potts, James; Ahmed, Rana; Aquart-Stewart, Althea; Cherkaski, Hamid Hacene; Denguezli, Meriam; Elbiaze, Mohammed; Elsony, Asma; Franssen, Frits M E; Ghobain, Mohammed Al; Harrabi, Imed; et al.
Summary: Background: Small airways obstruction is a common feature of obstructive lung diseases. Research is scarce on small airways obstruction, its global prevalence, and risk factors. We aimed to estimate the prevalence of small airways obstruction, examine the associated risk factors, and compare the findings for two different spirometry parameters. Methods: The Burden of Obstructive Lung Disease study is a multinational cross-sectional study of 41 municipalities in 34 countries across all WHO regions. Adults aged 40 years or older who were not living in an institution were eligible to participate. To ensure a representative sample, participants were selected from a random sample of the population according to a predefined site-specific sampling strategy. We included participants' data in this study if they completed the core study questionnaire and had acceptable spirometry according to predefined quality criteria. We excluded participants with a contraindication for lung function testing. We defined small airways obstruction as either mean forced expiratory flow rate between 25% and 75% of the forced vital capacity (FEF25–75 ) less than the lower limit of normal or forced expiratory volume in 3 s to forced vital capacity ratio (FEV3 /FVC ratio) less than the lower limit of normal. We estimated the prevalence of pre-bronchodilator (ie, before administration of 200 μg salbutamol) and post-bronchodilator (ie, after administration of 200 μg salbutamol) small airways obstruction for each site. To identify risk factors for small airways obstruction, we performed multivariable regression analyses within each site and pooled estimates using random-effects meta-analysis. Findings: 36 618 participants were recruited between Jan 2, 2003, and Dec 26, 2016. Data were collected from participants at recruitment. Of the recruited participants, 28 604 participants had acceptable spirometry and completed the core study questionnaire. Data were available for 26 443 participants for FEV3 /FVC ratio and 25 961 participants for FEF25–75 . Of the 26 443 participants included, 12 490 were men and 13 953 were women. Prevalence of pre-bronchodilator small airways obstruction ranged from 5% (34 of 624 participants) in Tartu, Estonia, to 34% (189 of 555 participants) in Mysore, India, for FEF25–75, and for FEV3 /FVC ratio it ranged from 5% (31 of 684) in Riyadh, Saudi Arabia, to 31% (287 of 924) in Salzburg, Austria. Prevalence of post-bronchodilator small airways obstruction was universally lower. Risk factors significantly associated with FEV3 /FVC ratio less than the lower limit of normal included increasing age, low BMI, active and passive smoking, low level of education, working in a dusty job for more than 10 years, previous tuberculosis, and family history of chronic obstructive pulmonary disease. Results were similar for FEF25–75, except for increasing age, which was associated with reduced odds of small airways obstruction. Interpretation: Despite the wide geographical variation, small airways obstruction is common and more prevalent than chronic airflow obstruction worldwide. Small airways obstruction shows the same risk factors as chronic airflow obstruction. However, further research is required to investigate whether small airways obstruction is also associated with respiratory symptoms and lung function decline. Funding: National Heart and Lung Institute and Wellcome Trust. Translations: For the Dutch, Estonian, French, Icelandic, Malay, Marathi, Norwegian, Portuguese, Swedish and Urdu translations of the abstract see Supplementary Materials section.